Perception of The Social Economy and Social Entrepreneurship by Students as Potential Entrepreneurs - Malgorzata Rembiasz (Communications of International Proceedings, 2020)
The article is an attempt to describe the perception of the social economy and social entrepreneurship as well as evaluate their prospects and obstacles to their development in the context of entrepreneurial intentions of students. From the point of view of academic research, the social economy is a broad and multifaceted phenomenon. Social enterprises try to combine activities complying with typical market mechanisms with social justice. The social economy is an element of policies aimed at ensuring sustainable development of the global economy. Local and national authorities, organisations (including the European Union) as well as international agencies and foundations launch different types of support instruments designed for social enterprises. The study carried out by means of an auditorium survey on a selected group of students has shown that they do not fully understand the concept of social economy. It is therefore worthwhile to take steps to enrich their knowledge about this sector and its benefits as part of a new approach to entrepreneurial education. Current socio-economic changes, including those recently caused by the coronavirus pandemic, call for new innovative solutions that would contribute to building a stronger society. Social entrepreneurship can develop fast if it is taken up by young, educated and creative people who are open to the world and social problems.
Keywords: Social Entrepreneurship; Social Economy; Entrepreneurial Intentions of Students.